Abordaje de la participación de los hombres rurales-campesinos de la Localidad de Sumapaz en la crianza, cuidado y protección de sus hijas e hijos, así como su influencia en las relaciones de género y nuevas masculinidades. (2024)
This state of the art emerges from research work conducted on rural peasant fatherhood specifically in the Sumapaz moorland of Colombia. For This purpose a tracking of academic production and bibliography was carried out at the international, national and regional levels from the years 2010 to 2023. Therefore it is structured in three parts. The fist part outlines the methodology that details the step by step process that guided the construction of the state of the art. In the second stage, various categories are addressed to contextualize, understand, and Approach caregiving, fatherhood and masculinity. Finally, the findings and gaps found in the reviewed documents are presented, leading to the conclusion that there are limited qualitative Studies on rural peasant fatherhood, which is favorable for our research. As for the methodology, the state of the art was supported by a hermeneutic approach.